La tramitación de los sumarios administrativos en las Juntas Distritales del Ministerio de Educación de Chimborazo y la aplicación del debido proceso - Alarcon Samaniego, Adriana (2022)
ABSTRACT The present investigative work is structured through three chapters, within the first chapter we find an analysis of administrative proceedings in Ecuadorian legislation, as well as the basic principles of administrative procedures, as well as the importance and development of administrative proceedings in legislation. Ecuadorian, the following chapter is structuring with an analysis of due process in administrative proceedings, its importance, and the rights concatenated in administrative proceedings that guarantee the application of due process, within the third chapter instead we find a legal study of due process in administrative proceedings developed by the District Boards, as well as the observance of the application of due process in the administrative proceedings developed by the District Boards, resulting in this investigation, that effectively the administrative proceedings were not developed Even in accordance with the established norms, in the same way the principle of due process is violated in their different rights. Keywords: Right to Defense, Due Process, Administrative Summaries.